Fundamentals of the presence of clergy in the media. Theological and canonical aspect - Kołodziej, Marcin (Kultura Media Teologia, 2025)
The Church carries out Christ's command to preach the Gospel also through the social media. This was pointed out in more recent times by the Second Vatican Council, which in its decree Inter mirifica, advocated the use of these tools. At the present time, the internet has also become an important space for the preaching of the word of God. The presence of clergy on social media seems necessary. Of course, it has its glows and shadows. Therefore, there is no shortage of indications in the Church's theological reflection and post-conciliar legislation to structure the ministry of clergy in the media in such a way that it becomes a modern pulpit and serves the effective preaching of the word of God.